Activity of human serum antibodies in an influenza virus hemagglutinin stalk-based ADCC reporter assay correlates with activity in a CD107a degranulation assay. Issue 8 (18th February 2020) - Chromikova, Veronika; Tan, Jessica; Aslam, Sadaf; Rajabhathor, Arvind; Bermudez-Gonzalez, Maria; Ayllon, Juan; Simon, Viviana; García-Sastre, Adolfo; Salaun, Bruno; Nachbagauer, Raffael; Krammer, Florian
Abstract: The stalk of the influenza virus hemagglutinin (HA) is an attractive target for antibody-based universal influenza virus vaccine development. While antibodies that target this part of the virus can be neutralizing, it has been shown in recent years that Fc receptor-mediated effector functions are of significant importance for the protective effect of anti-stalk antibodies. Several assays to measure Fc-Fc receptor interaction-based effector functions like antibody-dependent cellular cytotoxicity and antibody-dependent cellular phagocytosis exist, but they suffer from limitations such as low throughput and high run-to-run variability. Reporter assays for antibody-dependent cellular cytotoxicity based on reporter cells that express luciferase upon engagement of human FcγRIIIa with the Fc of antigen-bound antibodies have been developed as well. These reporter assays can be used in a higher throughput setting with limited run-to-run assay variability but since they express only one Fc receptor, their biological relevance is unclear. Here we optimized an antibody-dependent cellular cytotoxicity reporter assay to measure the activity of antibodies to the conserved stalk domain of H1 hemagglutinin. The assay was then correlated to a CD107a-based degranulation assay, and a strong and significant correlation could be observed. This data suggests that the FcγRIIIa-based reporter assay is a good substitute for functional assays, especially in settings where larger sample numbers need to be analyzed.